Evaluation of cardiopulmonary system outcomes in children with developmental coordination disorder: A systematic review - Martins R.* (2021)
© 2021 Elsevier B.V.Background: children with Developmental Coordination Disorder (DCD) tend to avoid physical activity, which can affect their health and well-being. Aim: Conduct a systematic review to identify, synthesize and compile data from the literature on the evaluation of the cardiopulmonary system in children with DCD. Method: According to PRISMA guidelines, we searched for articles indexed in PubMed, LILACS, Scopus, Web of Science, and Cochrane Library. The strategy was directed at the Population (children), Exposure (DCD), Outcomes (descriptors related to cardiopulmonary evaluation). Results: A total of 59 articles were identified through the databases. In the end, after analyzing the titles, abstracts, and full articles, including articles through manual search in the lists of bibliographic references, 13 articles relevant to the topic were included. All selected studies evaluated cardiorespiratory fitness / aerobic capacity parameters, and only three studies included the assessment of lung function. Conclusion: Although very heterogeneous, the evidence found in this review suggests that children with DCD have less cardiorespiratory fitness and lower lung function when compared to children with typical development. However, new studies are suggested to investigate and strengthen the evidence found in the present study.